O desenvolvimento da teoria do preço justo: Martín de Azpilcueta entre a originalidade e a tradição - Nascimento, Marlo do (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation aims to explore the theory of just price according to Martín de Azpilcueta (1492-1586), also known as Doctor Navarro, more specifically, it aims to highlight which elements in his theory are original and which ones reflect the influence of the medieval philosophical tradition. In order to reach such aim, in the first chapter the wide debate on just price in medieval philosophy prior to Azpilcueta is discussed, focusing on the following authors: Augustine of Hippo (354-430), Albert the Great (1200-1280), Thomas Aquinas (1225-1274), Peter John Olivi (1248-1298), Duns Scotus (1265-1308), Bernardino of Siena (1380-1444) e Antonino of Florence (1389-1459). The second chapter demonstrates that, in the 20th Century there is a process of retrieving ideas of the second scholastic by history researchers of the economical thinking and such process brings to light the discussion of themes related to economical philosophy approached by late 16th, early 17th Century authors, the writings of Martín de Azpilcueta are one of them. In the 21st Century there is significant interest on the ideas developed in the second scholastic by researchers worldwide, and to prove such thesis some research projects developed are presented. The third chapter focuses on the ideas of Martín de Azpilcueta and discusses the defense of the moral legality of the commercial activity as an assumption for the discussion of just price in Martin de Azpilcueta, found in his writtings Commentaria in septem distinctiones de poenitentia. The influence of Thomas Aquinas and Duns Scotus as concerns the discussion of such subject is also stressed. The fourth and last chapter approaches the theory of the just price of Doctor Navarro, which is discussed in his writings named Handbook of confessors and penitents. A more profound analysis of the theme is accomplished through the assessment of Azpicuelta’s just price theory in two editions of his Handbook, that is, in the Spanish edition of 1556 (Manual de confessores y penitentes), and in the Latin edition of 1573 (Enchiridion sive Manuale confessariorum et poenitentium), translated and revised by the author himself. Lastly, final considerations draw a parallel between original elements in the theory of just price of Azpilcueta and other elements resulting of his influence of the medieval philosophical tradition.
Keywords: Preço justo; Segunda escolástica; Martín de Azpilcueta; Just price; Second scholastic; Martín de Azpilcueta; ACCNPQ::Ciências Humanas::Filosofia